#### Answer

$\frac{12\div(2-5)+12(-1)}{2^{3} - (-4)^{2}} = 2$

#### Work Step by Step

$=\frac{12\div(2-5)+12(-1)}{2^{3} - (-4)^{2}}$
$=\frac{12\div(-3)-12}{8 - 16}$
$=\frac{-4-12}{8 - 16}$
$=\frac{-16}{-8}$
$=2$

Published by
Pearson

ISBN 10:
0321825535

ISBN 13:
978-0-32182-553-7

$\frac{12\div(2-5)+12(-1)}{2^{3} - (-4)^{2}} = 2$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.